Exploring ship traffic variability off California. (1st September 2018) - Moore, Thomas J.; Redfern, Jessica V.; Carver, Michael; Hastings, Sean; Adams, Jeffrey D.; Silber, Gregory K.
Abstract: Seaborne trade continues to grow and is an important component of the global economy. Threats from shipping to marine ecosystems include oil spills and other water pollution, air pollution, anchor scouring, biological invasions, container loss, chronic noise, and collisions between ships and large whales. Shipping and its associated threats can be influenced by a suite of regulations and economic events. The dynamic nature of ship traffic can be characterized using ship tracking data from automatic identification system (AIS) technology. These data enhance our ability to analyze the ecological threats from commercial shipping as a component of spatially explicit risk assessments. We explore ship traffic variability using a case study in waters off California. AIS data from 2008 to 2015 were used to evaluate the role of vessel emission regulations and economic events on vessel routes and speeds. We document vessels navigating around emission control areas (ECAs) or reducing speed when traveling through them. Large freight vessels decreased speeds from 2008 to 2015 by about 3–6 knots in many areas, with lowered speeds observed in areas of both heavy and sparse vessel use. The timing and location of the speed reductions appear to be most influenced by state and international clean fuel standards, which required the use of more costly fuels. Therefore, the speed reductions may have provided a more cost-effective means of travel. We also found temporary speed increases off southern California when vessels used longer routes to avoid traveling through an ECA. We conclude that the establishment of ECAs had a profound influence on vessel routes and speeds, likely due to the higher costs of clean fuels. Proposals have come before the International Maritime Organization (IMO) to establish clean fuel requirements in various locations around the world to reduce air-borne emissions from vessels. Our research suggests such proposals, or other events that may affect marine fuel prices, can have key impacts on vessel behavior. Consequently, it is important to consider this variability when designing strategies to minimize threats from shipping to vulnerable biophysical systems. Highlights: Maritime shipping is dynamic and poses threats to cetaceans and ecosystems. Fuel regulations trigger vessel traffic changes (routing and speed changes). Economic events and regulations at various scales influence vessel behavior. Emission control areas and fuel prices can be important drivers of ecological risk. Results show import of shipping variability in spatially explicit risk assessments.